Liquid Consumption - Bardhi, Fleura; Eckhardt, Giana M (Journal of Consumer Research, 2017)
Abstract This article introduces a new dimension of consumption as liquid or solid. Liquid consumption is defined as ephemeral, access based, and dematerialized, while solid consumption is defined as enduring, ownership based, and material. Liquid and solid consumption are conceptualized as existing on a spectrum, with four conditions leading to consumption being liquid, solid, or a combination of the two: relevance to the self, the nature of social relationships, accessibility to mobility networks, and type of precarity experienced. Liquid consumption is needed to explain behavior within digital contexts, in access-based consumption, and in conditions of global mobility. It highlights a consumption orientation around values of flexibility, adaptability, fluidity, lightness, detachment, and speed. Implications of liquid consumption are discussed for the domains of attachment and appropriation; the importance of use value; materialism; brand relationships and communities; identity; prosumption and the prosumer; and big data, quantification of the self, and surveillance. Lastly, managing the challenges of liquid consumption and its effect on consumer welfare are explored.